Equação de Liouville e superfícies mínimas sem pontos umbílicos - Amaral, Luís Fernando Coelho (2003)
This dissertation is based on the article Revisiting the Connection between Minimal Surface and Solutions of the Liouville Equation, where a modern approach of these classic questions is presented. Chapter 1 deals with some basic properties of minimum surfaces and introduces the notion of Liouville's parameter. In chapter 2 we will make a brief study of the representation of Enneper-Weierstrass satisfying certain conditions produces a solution of the Liouville equation. Chapter 3 is focused on some classic examples of minimum surfaces and their parameterizations through Weierstrass representation and also for an analysis of the symmetric solutions of the Liouville equation.